Transforming learning through strategic management case studies : OUM's on-line alternative - Wardah Mohamad; Zorah Abu Kasim; Tuan Fatma Tuan Sulaiman (2012)
Engaging learners has become a major topic of discussion amongst academicians as many employers in the corporate sector have voiced their complaints regarding the employability of local graduates. Our local graduates are said to lack critical thinking skills and analytical abilities. Taking this in mind, the Faculty of Business and Management of Open University Malaysia has embarked on an ambitious project to engage learners using case studies in Strategic Management. The use of cases as a tool to develop critical thinking and analytical abilities have long been used by renowned business schools such as Harvard Business School in the United States and Curtin Business School in Australia. OUM’s Faculty of Business and Management has gone a step further to transform learning for its students – the Strategic Management course is going to be offered fully on-line where the faculty’s academicians will engage in case discussions with learners from anywhere in the country at any point of time. The use of cases, supplemented by learning materials, Power Point slides and videos will foster a more engaging learning environment where learners will experience real-life scenarios, make decisions and formulate strategies in the shoes of CEOs. This paper will share the faculty’s plans and implemented projects for the transformation of BBPS4103 Strategic Management. (Abstract by authors)